Quality of life in cervical dystonia after treatment with botulinum toxin a: A 24-week prospective study - Kongsaengdao S. (2017)
© 2017 Kongsaengdao et al. Objective: This study aimed to identify possible improvements in disease-specific health-related quality of life (HRQoL) after multiple injections of botulinum toxin A over 24 weeks in Thai cervical dystonia (CD) patients. Materials and methods: A 24-week prospective study comparing HRQoL of Thai CD patients before and after multiple injections of botulinum toxin A at 3-month intervals was performed. Disease-specific HRQoL was assessed by using the Cervical Dystonia Impact Profile-58 questionnaire (CDIP-58) and the Craniocervical Dystonia Questionnaire-24 (CDQ-24). General HRQoL was assessed by using the Medical Outcomes’ 36-Item Short Form Health Survey (SF-36) and the EuroQoL 5-dimension questionnaire (EQ-5D). All the assessments were performed before and after the 24-week treatment period. Results: A total of 20 CD patients were enrolled in this study from April to December 2011. CDIP-58 and CDQ-24 scores, which assess disease-specific HRQoL, showed a significant improvement after 24 weeks of treatment by botulinum toxin A (P < 0.001). However, EQ-5D and SF-36 scores, which assess general HRQoL, showed no significant improvement after the treatment (P > 0.05). Conclusion: CD patients’ disease-specific HRQoL improved after being treated with multiple botulinum toxin A injections. However, general HRQoL was not improved.